What do complementary and alternative medicines mean to UK dairy farmers and how do they use them? - Crouch, Kayleigh M.; Cramer, Helen; Rees, Gwen M.; Sharp, Debbie; Barrett, David C.; Cabral, Christie (Frontiers in Veterinary Science, 2025)
BackgroundComplementary and alternative medicine (CAM) is used by some farmers to support herd health management practices. There is concern by a large majority of the veterinary community, who consider CAM to be counter to evidence-based practice. Little is known about what and how CAM is used on farms, and it is not clear which products or practices are encompassed by what farmers consider to be CAM. This paper reports on a study exploring the use of CAM on dairy farms in the UK.MethodsTwenty farms with a range of management systems and herd sizes were recruited. Interviews were conducted with 24 farmers via face-to-face, telephone or videoconferencing modalities necessitated by the Covid-19 movement restrictions. 16 farms were visited to collect observational data using ethnographic fieldnotes and photographs. Interviews were conducted using topic guides and explored participants’ experience of CAM and potential influence on antibiotic use. Interviews were audio recorded, transcribed, and thematically analysed using NViVo software.ResultsA range of views and conceptualisation of CAM was identified among the participating dairy farmers. CAM was not usually seen as one particular product or health management tool but encompassed a range of health management strategies and philosophies. Results indicated that some farmers explore and engage with a range of complementary and alternative medicines and approaches to animal health on dairy farms. Some farmers considered food products, shop bought products, environmental enrichment, in-depth animal observations and technology to form part of their CAM approach. Farmers associated CAM with holistic health management and animal welfare. CAM formed part of a wider ethos regarding holistic farming and land use and was sometimes used to support them in avoiding overuse of antibiotics.DiscussionFarmers use CAM, and their conceptualisation of it is complex. Several resources and stakeholders were consulted by farmers to understand CAM and conventional medicine. Farmers interest in CAM warrants further consideration. This may support dairy farmers to reduce antimicrobial use responsibly, with veterinary support.